(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2026)
The emerging development characteristics of the global economy influence the operational strategies of market participants, as well as the management mechanisms and mindsets of executives. At the current stage of economic development, the orientation toward innovation has become a priority vector for the economic growth of every state. This trend is primarily reflected both in ongoing scientific research and in the practical operations of economic entities. Under contemporary economic conditions driven by industrialization policies, the electrical engineering industry- as the newest sector of mechanical engineering is considered the most pivotal field in terms of its potential capabilities and is widely utilized across all sectors of the national economy. The specific characteristics of the electrical engineering industry, which plays a crucial role in the economic life of our country amidst an intensifying competitive environment, along with the evaluation of its impact on meeting economic demands, define the relevance and timeliness of this research.